Introduction to geographic information systems - Chang, Kang-Tsung (New York McGraw-Hill, 2010)
Accompanying CD-ROM contains data sets to be used in conjunction with ArcGIS 9.2 to complete tasks in the text.
McGraw-Hill international edition.
Includes bibliographical references and index.
Accompanying CD-ROM system requirements: Windows 2000, XP,Pentium 233 MHz or better, 32 MB RAM, 4 x CD-ROM drive, (16x or better recommended).
Keywords: Geographic information systems